TRANSFORMASI PENDIDIKAN AGAMA ISLAM TERHADAP MEDIA SOSIAL INSTAGRAM - M. Masyrik; Syamsul Aripin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of Information and Communication Technology (ICT), particularly in the transformation of Islamic religious education through the social media platform Instagram, has brought significant changes in the way religious information is delivered and received. Instagram has seen growth in various sectors, including education. It also offers new opportunities in Islamic Religious Education (PAI), especially in enhancing accessibility to learning materials and facilitating interaction between teachers and students. However, the use of Instagram also presents challenges, such as the spread of misinformation or hoaxes. This study aims to analyze how Instagram is used as a tool for Islamic religious education and its impact on users’ understanding and religious practices. The research method employs a qualitative approach through content analysis and in-depth interviews.